ANALISIS FAKTOR RISIKO MUSCULOSKELETAL DISORDER (MSDs) PADA PEKERJA PETIK TEH DI PT X KAYU ARO - Nurftah, Lutviyah; Rini, Willia Novita Eka; Ibnu, Ismi Nurwaqiah (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2022)
ABSTRACT Background: Musculoskeletal complaints look trivial but have a general impact on tea picking workers which will later affect the worker’s performance. The purpose of this study is to analyze risk factors that affect complaints of Musculoskeletal Disorders (MSDs) in tea picking workers at PT X Kayu Aro judging from several factors namely Age, gender, working period, work posture, workload, transport distance and duration of working. Method: Research Design is Cross Sectional. The sample technique used is Proposional random sampling with a sample number of 81 tea picking workers at PT X KayuAro. Bound variables are complaints of musculoskeletal disorders (MSDs) and free variables are individual factors and work factors (Genderi,, iAge, period iWork, working posture, transport distance, Duration ofWork). Data collection is conducted using NBM methods and OWAS measurements, while on data analysis using chi squaretest. Results: The proportion of complaints of musculoskeletal disorders among tea picking workers at PT X Kayu Aro is (78.6%) with MSDS complaints. There was a relationship between age (PR=1,760; 95% CI: 1,712-17,165), years of service (PR=1,476;95% CI: 1,720-19,290), weight of load (PR=1,402;95% CI: 1,412-15,744), duration of work (PR=1.409; 95% CI: 1.315-11.022) and there was no relationship between gender, work posture and transport distance. Conclusion: Factors that affect the risk of complaints of musculoskeletal disorders in tea picking workers at PT X Kayu Aro include age, gender, working period, workload and duration of work. Therefore, it is advisable for workers to pay attention to working hours and can also be heavy burdens that are makasimal to minimize complaints of musculoskeletal disorder. Keywords: Tea Picking Workers, Musculoskeletal Di sorders,Risk Factors ABSTRAK Latar Belakang : Keluhan musculoskeletal terlihat sepele namun berdampak serius pada pekerja petik teh yang nantinya akan mempengaruhi kinerja pekerja. Tujuan dari penelitan ini adalah menganalisis faktor risiko yang mempengaruhi keluhan Musculoskeletal Disorders (MSDs) pada pekerja petik teh di PT X Kayu Aro dilihat dari beberapa faktor yaitu Usia, jenis kelamin, masa kerja, postur kerja, beban kerja, jarak angkut dan durasi kerja. Metode : Desain Penelitian adalah Cross Sectional. Teknik sampel yang digunakan yaitu Proposional random sampling dengan jumlah sampel 81 pekerja petik teh di PT X Kayu Aro. Variabel terikat adalah keluhan musculoskeletal disorders (MSDs) dan variabel bebas adalah faktor individu dan faktor pekerjaan (Jenis Kelamin, Usia, masa Kerja, postur kerja, jarak angkut, Durasi Kerja). Pengumpulan data dilakukan wawancara dengan menggunakan metode NBM dan pengukuran OWAS, sedangkan pada analisis data menggunakan uji Chi square. Hasil : Proporsi keluhan musculoskeletal disorders pada pekerja petik teh di PT X Kayu Aro adalah (78,6%) merasakan keluhan MSDS. Ada hubungan antara usia (PR=1,760;95% CI: 1,712-17,165), masa kerja (PR=1,476;95% CI: 1,720-19,290), berat beban (PR=1,402;95% CI: 1,412-15,744), durasi kerja (PR=1,409; 95% CI: 1,315-11,022) dan tidak ada hubungan antara jenis kelamin, postur kerja dan jarak angkut. Kesimpulan :Faktor yang mempengaruhi munculnya risiko keluhan musculoskeletal disorders pada pekerja petik teh di PT X Kayu Aro diantaranya usia, masa kerja, beban kerja dan durasi kerja. Maka dari itu disarankan bagi para pekerja agar memperhatikan jam kerja dan juga dapat berat beban yang maksimal untuk menimimalisir keluhan musculoskeletal disorder. Kata Kunci : Pekerja Petik Teh, Musculoskeletal Disorders, Faktor Risiko